Tugging at hairstrings hair embroidery as a metaphor for adoption - Conanan, Sarah Mae M.; Concepcion, Reynaldo L.
Family is the core group that helps identify and mould a person. Unfamiliarity with the concept of or the physical absence of the family can cause an individual to experience a feeling of incompleteness. The proponent confronts this feeling of incompleteness and uncertainty brought about by the knowledge of her adoption from birth.